A comparative study of penalty or levy implementation at state level in Peninsular Malaysia / Nurul Azreen Syamira Azlan and Nor Azalina Yusnita Abdul Rahman - Azlan, Nurul Azreen Syamira; Abdul Rahman, Nor Azalina Yusnita (2023)
National Affordable Housing Policy allows states to impose penalties or levies on developers who get exemptions from developing affordable housing. However, its implementation is not uniform and only seven states have implemented it and categorized as fixed percentage (Perak), range of percentage (Kelantan), and fixed value (Terengganu, Kedah, Pahang, Melaka, and Johor). The research aims to identify similarities and differences between implementation of penalties or levies for the exemption from developing affordable housing at the state level. The research is qualitative research and structured interview session is used to collect data. The chosen states as respondents for each category are Perak, Kelantan and Terengganu. Research findings show that all states implement penalty or levy to support national policies and use fund to redevelop exempted affordable housing units. The exemption application process involves developers applying to each state government, conducting an investigation, and deciding whether to approve or reject the application through "Majlis Mesyuarat Kerajaan Negeri”. For differences, penalty or levy rate is determined based on one-to-one basis, cost of construction, location and project feasibility and affordable housing prices is determined by the state governments. The effects of this implementation vary, such as fluctuating open price housing units, decreasing supply and demand mismatch, and preventing developers from taking advantage of exemption granted. Therefore, future researchers should study the most suitable amount of penalty or levy for private developers to ensure uniformity and increase efficiency in affordable housing development in Malaysia.